أسباب عزوف الشباب على الزواج - راضية, لبرش (Sciences de l'Homme et de la Société, 2017)
إن ظاهرة عزوف الشباب المثقف عن الزواج من الظواهر التي تنخر في جسم المجتمع وتهدد استقراره، حيث باتت ظاهرة ترهق كيان الأسرة و المجتمع على حد سواء، نظرا لطبيعة المشكلات وحجمها، ومن أهم المشكلات التي أصبح يتخبط فيها الشاب المثقف هي حالة اللاستقرار، والتي تنعكس سلبا على حياته و حياة من حوله، وعلى استقرار و استمرار الأسرة وتقدم وتطور المجتمع. حيث لا تزال الأسباب الاقتصادية هي البارزة وراء عزوف الشباب عن الزواج وخاصة غلاء المهور و أزمة السكن، بالإضافة إلى توسع دائرة التعارف و الاحتكاك و الاختلاط بفضل التطور التكنولوجي و في مقدمتها مواقع التواصل الاجتماعي.   Abstract : The phenomenon of the reluctance of educated youth to marry phenomena that degenerate in the body of society and threaten its stability, where the phenomenon is becoming burdensome entity of the family and society alike, given the nature of the problems and size, and one of the most important problems that floundering young intellectual is a state of instability, which Reflected negatively on his life and life around him, and on the stability and continuity of the family and progress and development of society. Where economic reasons are still prominent behind the reluctance of young people to marry, especially the high cost of ponies and the housing crisis, in addition to the expansion of the circle of acquaintance and friction and mixing thanks to technological development, especially social networking sites .